Family factors and health behaviour of thin adolescent boys and girls. (16th September 2016) - Mason, Anna; Rantanen, Anja; Kivimäki, Hanne; Koivisto, Anna‐Maija; Joronen, Katja
Abstract: Aim: The aim of this study was to examine prevalence of extreme thinness and thinness in adolescent boys and girls and to study associations between family factors, health behaviour and thinness in boys and girls. Background: Extreme thinness carries high health risks. The family and health behavioural factors related to adolescent thinness have not been studied previously using a nationally representative data. Design: This is a cross‐sectional quantitative study. Methods: The nationally representative data were obtained from the Finnish School Health Promotion study conducted in 2013. The sample of this study included 12‐17 year old adolescents ( n  = 71, 973) who were categorised as extremely thin, thin and normal weight using international age and gender body mass index (BMI) cut‐off points for children and adolescents. Associations with family factors and health behaviour were examined separately for boys and girls using cross‐tabulations, Chi‐square test and multinomial logistic regression. Results: Thinness and extreme thinness were more common in girls than in boys. Health behaviour, such as smoking and exercise, were associated with thinness and extreme thinness in both genders. Regarding family factors; low maternal education, family meal and parental knowledge of adolescents' friends and whereabouts were associated with thinness and, or extreme thinness in both boys and girls. However, there were gender differences in the associations. Conclusions: It is important for healthcare professionals working with adolescents to be aware of prevalence in thinness and aware of health behaviour and family factors that are associated with thinness and extreme thinness in adolescence.